2020
DOI: 10.1111/1744-7917.12897
|View full text |Cite
|
Sign up to set email alerts
|

Inductive and synergistic interactions between plant allelochemical flavone and Bt toxin Cry1Ac in Helicoverpa armigera

Abstract: Genetically engineered crops simultaneously produce defensive allelochemicals and Bacillus thuringiensis (Bt) toxin proteins to kill some of the world's most devastating insect pests. How the two types of toxins, when ingested sequentially or simultaneously, interact at both lethal and sublethal doses in these pests remains underexplored. Here, we examined the toxicological interactions between the Bt toxin Cry1Ac and the flavonoid allelochemical flavone in Helicoverpa armigera. Simultaneous exposure of H. arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Plant secondary metabolites like phenols, alkaloids, flavonoids, and terpenes have been shown to impede the growth and population development of insects [ 2 , 3 , 4 ]. These toxic metabolites are difficult to digest or are neurotoxic to insects [ 2 , 5 ]. In response, insects have evolved diverse strategies, including detoxification enzymes, such as cytochrome P450 (P450s) monooxygenases, carboxylesterases, and glutathione S-transferases (GSTs), to adapt to different host plants and detoxify phyto-toxins [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant secondary metabolites like phenols, alkaloids, flavonoids, and terpenes have been shown to impede the growth and population development of insects [ 2 , 3 , 4 ]. These toxic metabolites are difficult to digest or are neurotoxic to insects [ 2 , 5 ]. In response, insects have evolved diverse strategies, including detoxification enzymes, such as cytochrome P450 (P450s) monooxygenases, carboxylesterases, and glutathione S-transferases (GSTs), to adapt to different host plants and detoxify phyto-toxins [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported synergistic cases are azadirachtin + Bacillus thuringiensis Berliner sub sp. kurstaki against H. armigera [32], maize insect resistance cysteine protease (Mir1-CP) + Cry2A against Helicoverpa zea, H. virescens, Spodoptera frugiperda, and Diatraea grandiosella [33], gossypol + Cry1Ac against a resistant strain of H. zea [34], jasmonic acidinduced resistance plus Cry1Ac or Cry1Ac + Cry2Ab against S. frugiperda [35], and flavone + Cry1Ac against H. armigera [36]. The antagonistic cases are tannis + Cry1Ac against H. armigera [37], quercetin + Cry1Ac against H. armigera [38], and Bt + trichlorfon against Plutella xylostella [39].…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported synergistic cases are azadirachtin + Bacillus thuringiensis Berliner sub sp. kurstaki against H. armigera [ 32 ], maize insect resistance cysteine protease (Mir1-CP) + Cry2A against Helicoverpa zea , H. virescens , Spodoptera frugiperda, and Diatraea grandiosella [ 33 ], gossypol + Cry1Ac against a resistant strain of H. zea [ 34 ], jasmonic acid-induced resistance plus Cry1Ac or Cry1Ac + Cry2Ab against S. frugiperda [ 35 ], and flavone + Cry1Ac against H. armigera [ 36 ]. The antagonistic cases are tannis + Cry1Ac against H. armigera [ 37 ], quercetin + Cry1Ac against H. armigera [ 38 ], and Bt + trichlorfon against Plutella xylostella [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antagonistic cases are tannis + Cry1Ac against H. armigera [ 37 ], quercetin + Cry1Ac against H. armigera [ 38 ], and Bt + trichlorfon against Plutella xylostella [ 39 ]. So far, there has been only one sequential ingestion case study, which showed that pre-exposure to Cry1Ac significantly induced flavone’s toxicity against H. armigera , whereas pre-exposure to flavone did not induce or inhibit Cry1A’s toxicity against the same pest species [ 36 ].…”
Section: Introductionmentioning
confidence: 99%